PEDAGOGI EKSISTENSIAL HUMANISTIK DALAM PANDANGAN JEAN PAUL SARTRE DAN REFLEKSI ATAS KEBIJAKAN MERDEKA BELAJAR DI INDONESIA - Siswadi, Gede Agus (Fakultas Dharma Acarya IAHN-TP Palangka Raya, 2024)
This research focuses on an exploration of Jean Paul Sartre’s thoughts related to the philosophy of existentialism. The philosophical thinking of this existentialist will form a stream of existentialist education philosophy that is more inclined to the application of humanistic education. The method used in this research is a qualitative method with a philosophical hermeneutic approach. The results of this study show that humanistic existentialist pedagogy is an educational approach that prioritises the individuality and subjective experience of students. Rooted in the philosophies of existentialism and humanism, this approach positions teachers as facilitators who help students find the meaning of life, develop identity, and explore personal values. The main focus is to empower students to take an active role in the learning process, encourage self-reflection and build independence. Through deep interaction between students and subject matter, this approach triggers holistic development, not only of cognitive aspects but also emotional, social, and spiritual. Teachers not only teach facts, but also guide students in relating learning to the reality of everyday life. It aims to create individuals who are more aware, responsible, and have a deeper understanding of themselves as well as the surrounding environment. The humanistic existentialist pedagogical approach and the concept of ‘Merdeka Belajar’ both prioritise individual autonomy in learning. Both the humanistic existentialist approach, which emphasises personal growth and freedom in learning, and the concept of ‘Merdeka Belajar’, which gives students the opportunity to manage their own learning, both provide space for students to take an active role in the learning process, respect the uniqueness of each individual, and encourage personal responsibility in learning from each learner.